The Preparation for the Cooperativisation of the Polish Rural Youth Not Included in School Teaching during the Interwar Period (1918–1939) - Magiera, Elżbieta (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2014)
The output of the XXth century Polish cooperative movement can be considered in ideological, organisational, economic, social and educational terms. The cooperative movement had a ignificant effect on the educational and propagating activities for both adults and school children. The cooperative movement criticized egoism and the pursuit of profit, taught cooperative forms of work, mutual help, and solidarity as well as providing the basic necessities for the poor. It supported the family and the education of children, young people and adults. It propagated the development of student organizations, the cooperative education and upbringing through taking cooperation into consideration in curricula. Cooperative education was created at the Polish cooperative movement’s initiative.
Keywords: cooperative movement; preparation for cooperation; interwar period; rural; agriculture education